2005
DOI: 10.1515/jpem.2005.18.2.133
|View full text |Cite
|
Sign up to set email alerts
|

Update on the Prenatal Diagnosis and Treatment of Congenital Adrenal Hyperplasia due to 11β-Hydroxylase Deficiency

Abstract: 11beta-Hydroxylase deficiency is a common form of congenital adrenal hyperplasia causing virilization of the female fetus and hypertension. DNA analysis of the gene (CYP11B1) encoding 11beta-hydroxylase has been reported previously to be effective in the prenatal diagnosis of one affected female fetus. In that case, prenatal treatment with dexamethasone resulted in normal female genitalia. We now report five new pregnancies that underwent prenatal diagnosis for 11beta-hydroxylase deficiency. In the first famil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 20 publications
(11 reference statements)
1
6
0
Order By: Relevance
“…We found that 41 compound heterozygotes or homozygotes for select missense or nonsense mutations-namely P49L, R141Q, W260X, G267S, L299P, T318M, T318R, A331V, Q356X, A368D, R374Q, V441G, G444D, G446V, and R448H-present with moderate to severe classic CAH because of 11β-hydroxylase, confirming prior results (3,(14)(15)(16)(17)(22)(23)(24). These patients were mainly from Croatia, Tunisia, Africa, Turkey, and Saudi Arabia.…”
Section: Discussionsupporting
confidence: 88%
“…We found that 41 compound heterozygotes or homozygotes for select missense or nonsense mutations-namely P49L, R141Q, W260X, G267S, L299P, T318M, T318R, A331V, Q356X, A368D, R374Q, V441G, G444D, G446V, and R448H-present with moderate to severe classic CAH because of 11β-hydroxylase, confirming prior results (3,(14)(15)(16)(17)(22)(23)(24). These patients were mainly from Croatia, Tunisia, Africa, Turkey, and Saudi Arabia.…”
Section: Discussionsupporting
confidence: 88%
“…Tunisians often carry the two mutations, G379 V and Q356X [ 24 ], of which Q356X is also common among sub-Saharan Africans and African-Americans [ 2 , 3 , 24 26 ]. The T318 M mutation is most common among Yemenis [ 2 , 27 , 28 ], and some new mutations such as c.53_54insT, G206 V, W260X, R448P, and H465L are often found in Saudi Arabs [ 29 31 ]. The R454C mutation has only been reported among the Chinese [ 8 , 10 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…The one, p.R448H, is most frequently found in almost all affected alleles (23 alleles) of Moroccan Jews [5,13] but also in Caucasian patients (7 alleles) [35,36]; the other, p.R448C, is rare (2 alleles) [5,35]. Another mutation, p.G444D, modifies a Gly conserved in CYP11B1 species and steroidogenic cytochromes but not other cytochromes, and decreases 11β-hydroxylase activity [37]. Finally, our third new mutation, p.A259D, changes Ala259 conserved only in mitochondrial enzymes and located in the helix G according to our modeling.…”
Section: Discussionmentioning
confidence: 99%